2007
DOI: 10.1104/pp.106.095562
|View full text |Cite
|
Sign up to set email alerts
|

The Transiently Generated Nonphotochemical Quenching of Excitation Energy in Arabidopsis Leaves Is Modulated by Zeaxanthin

Abstract: Upon the transition of dark-adapted plants to low light, the energy-dependent quenching (qE) of excitation energy is only transiently induced due to the only transient generation of the transthylakoid pH gradient. We investigated the transient qE (qE(TR)) in different Arabidopsis (Arabidopsis thaliana) mutants. In dark-adapted plants, qE(TR) was absent in the npq4 mutant (deficient in the PsbS protein) and the pgr1 mutant (restricted in lumen acidification). In comparison with wild-type plants, qE(TR) was redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 44 publications
4
29
1
Order By: Relevance
“…Previously, qE formed under these conditions was ascribed to quenching in the PSII reaction center (Finazzi et al, 2004), but here it was shown to be accompanied by an absorption change with the same spectrum as that associated with steadystate qE formed in high light. It was also shown that the transient qE was affected by alteration in the xanthophyll composition in the same way as steady-state qE, adding to previous results (Kalituho et al, 2007); thus, the transient qE was strongly reduced in lut2 and lut2npq2 and completely absent in the lut2npq1 mutant. When combined with the reported dependence of transient qE upon PsbS (Finazzi et al, 2004;Kalituho et al, 2007), these data strongly suggest that it originates from the same common PSII antenna-based mechanism as steady-state qE in high light.…”
Section: Discussionsupporting
confidence: 62%
“…Previously, qE formed under these conditions was ascribed to quenching in the PSII reaction center (Finazzi et al, 2004), but here it was shown to be accompanied by an absorption change with the same spectrum as that associated with steadystate qE formed in high light. It was also shown that the transient qE was affected by alteration in the xanthophyll composition in the same way as steady-state qE, adding to previous results (Kalituho et al, 2007); thus, the transient qE was strongly reduced in lut2 and lut2npq2 and completely absent in the lut2npq1 mutant. When combined with the reported dependence of transient qE upon PsbS (Finazzi et al, 2004;Kalituho et al, 2007), these data strongly suggest that it originates from the same common PSII antenna-based mechanism as steady-state qE in high light.…”
Section: Discussionsupporting
confidence: 62%
“…4). This was a clear indication that the xanthophyll cycle is not required to induce the PsbSdependent quenching but that it strongly modulates the strength of thermal dissipation, as was shown recently (Kalituho et al, 2007).…”
supporting
confidence: 71%
“…No difference in the NPQ transiently generated in dark-adapted leaves from the wild type, ndho-1, and trxm4-1 exposed to low light could be recorded (Supplemental Fig. S5C), indicating that transient generation of the transthylakoidal pH gradient (Kalituho et al, 2007) was similar in wild-type and mutant plants. Knocking out genes encoding NDH subunits either in tobacco (Burrows et al, 1998;Kofer et al, 1998;Shikanai et al, 1998) or in Arabidopsis Shikanai, 2007) did not affect overall photosynthetic electron transport, and plants did not display any visible phenotype.…”
Section: Discussion Trxm4 Controls the Ndh-and Pgr-dependent Pq Reducmentioning
confidence: 96%